Front Cover: Advances in glycopeptide enrichment methods for the analysis of protein glycosylation over the past decade. Issue 16 (26th August 2022) - Li, Jiajia; Zhang, Jie; Xu, Mingming; Yang, Zeren; Yue, Shuang; Zhou, Wanlong; Gui, Chunshan; Zhang, Haiyang; Li, Shuwei; Wang, Perry G.; Yang, Shuang
Abstract : DOI: 10.1002/jssc.202200292 The cover picture shows different techniques for enriching glycopeptides using diverse schemes. The digested peptide mixtures are interacted with HILIC, GIG, SPEG or lectins for specific analysis of glycopeptides, including intact glycopeptides, O‐glycopeptides, N‐glycosites and different types of glycopeptides are targeted, respectively.